Maternofetal outcomes in early versus late onset pre-eclampsia: a comparative study - Shankar, Poornima; Karthikeyan, Kavitha; Nalini, Amrita Priscilla; M., Sindhura; Kim, Gowtham (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Preeclampsia is being increasingly recognized as two different entities: early-onset preeclampsia occurring at less than 34 weeks of gestation, and late-onset disease occurring at 34 or more weeks of gestation. Early-onset and late-onset pre-eclampsia are found to have different implications for the mother and neonate. The aim of this study is to compare the risk factors, maternal and fetal outcomes in early (<34 weeks) versus late (≥34weeks) onset preeclampsia. Methods: 208 patients diagnosed with pre-eclampsia in Chettinad Academy of Research and Education over a period of three years (From January 2014 to December 2016) were retrospectively studied. Patients were classified as early onset and late onset pre-eclampsia based on the gestational age of onset. Data on risk factors, maternal and fetal outcomes were collected and analyzed using Chi Square and Fisher’s test and compared. Results: The overall preeclampsia rate was 6.3%. Early onset and late onset were 34.6% and 65.3% respectively and the rate increased with increasing gestational age.35.3% of patients with late onset preeclampsia and 55.6% patients of early onset type required more than one drug which is a statistically significant difference. Proteinuria more than 3gm/l/day was significantly more in late onset preeclampsia than in early onset preeclampsia. 55.5% of patients with early onset pre-eclampsia required MgSO4 when compared to 17.4%. There was no statistically significant difference in the rate of caesarean section (61.1% vs 73.5%). Altered coagulation profile was significantly more in early onset preeclampsia (11.1%). The incidence of oligohydramnios, SGA and low APGAR at 5 minutes of birth were significantly high in early onset pre-eclampsia when compared to late onset type. Conclusions: Patients with early onset pre-eclampsia are found to have significantly higher rates of specific maternal and fetal morbidity when compared to the late onset type.